Correction: The salivary microbiota of patients with acute lower respiratory tract infection-A multicenter cohort study. - Matthew B Rogers; Ashley Harner; Megan Buhay; Brian Firek; Barbara Methé; Alison Morris; Octavia M Peck Palmer; Susan B Promes; Robert L Sherwin; Lauren Southerland; Alexandre R Vieira; Sachin Yende; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0290062.].